"You don't really see the dangers of it at the time." Risk perceptions and behaviours of older female gamblers. (March 2021) - McCarthy, Simone; Thomas, Samantha L.; Pitt, Hannah; Bellringer, Maria E.
Abstract: Older women are vulnerable to the risks associated with some forms of gambling. While research has examined how individuals functionally interact with gambling products, very limited research has investigated how individuals conceptualise and interpret the risks associated with these products. Theorists suggest that risk-taking is not based on a lack of knowledge but on the different ways people make sense of their lives. As such, this study aimed to understand the factors that may influence how older women who gamble on electronic gambling machines (EGMs) perceive the risks associated with gambling on these products. It examined how risk perceptions interacted with a range of complex social factors in women's everyday lives to influence their risk behaviours. Semi-structured interviews were conducted with 20 Australian women aged 55 and over who had been negatively impacted by EGM gambling. This study found that older women's risk perceptions of gambling were shaped by their early recreational experiences with gambling, rather than their current regular and harmful gambling behaviours. Risk perceptions of EGMs were often downplayed or ignored as women sought to maintain valued social identities within the venues. Women went through a process of risk negotiation whereby the benefits of this social interaction outweighed the potential harms associated with the machines. This also led them to deflect or ignore risk minimisation messaging which was completely focused on individual behaviours. This study signals the importance of moving away from individualised responsible gambling messages towards risk information about gambling products. This research also provides evidence of the need for regulation addressing the design features of EGMs that ultimately may make products safer and protect the most vulnerable from gambling harm. Highlights: Qualitative interviews with older women impacted by gambling. Gambling became an integral part of women's identities for social connection. Gambling was perceived to meet older women's social and emotional needs. Misinformation about structural characteristics of electronic gambling machines. Older women may justify the risks of gambling when benefits that outweigh harms.